Homosexuality and the Christian : [a guide for parents, pastors, and friends] - Yarhouse, Mark A., 1968- (Bloomington, MN : Bethany House Publishers, 2010)
"A leading Christian psychologist and researcher answers questions about same-sex relationships and sexual identity with clarity and empathy"--Provided by publisher.
The big picture -- What does god think about homosexuality? -- Why is sexual identity the heart of the matter? -- What causes homosexuality? -- Can someone change sexual orientation? -- Honest answers to questions facing families -- What if my child or teen announces a gay identity? -- My adult child announced a gay identity : what now? -- What if my spouse announces a gay identity? -- Questions for the church -- Whose people are we talking about? -- What is the church's response to enduring conditions? -- Concluding thoughts.
Includes bibliographical references (p. [219]-239).
Keywords: Homosexuality; Homosexuality -- Psychological aspects; Homosexuality -- Religious aspects -- Christianity